Development of wheat gluten/nanocellulose/titanium dioxide nanocomposites for active food packaging. (25th June 2015) - El-Wakil, Nahla A.; Hassan, Enas A.; Abou-Zeid, Ragab E.; Dufresne, Alain
Highlights: New nanocomposite from gluten, cellulose nanocrystals, and titanium dioxide nanoparticles was prepared. Cellulose nanocrystals and titanium dioxide nanoparticles improves mechanical are water barrier properties of gluten films. Paper sheets coated with the aforementioned nanocomposite. Coated paper sheets showed good antimicrobial activity against G +ve and G −ve bacteria and yeast. Abstract: Bionanocomposites were developed by casting/evaporation of wheat gluten (WG), cellulose nanocrystals (CNC), and TiO2 nanoparticles. The effect of addition of different percentages of CNC, and TiO2 on tensile strength (TS), Young's modulus and water sensitivity was studied. A significant improvement in the studied properties is observed when 7.5% CNC and 0.6% TiO2 is added to WG. WG/CNC 7.5%/0.6% TiO2 blend suspension was chosen to coat commercial packaging unbleached kraft paper sheets via 1, 2 and 3 coating layers. A significant enhancement of 56% and 53% in breaking length and burst index, respectively, was achieved for 3 layers coated paper. The antimicrobial activity of the coated papers, against Saccharomyces cervisiae, Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus, was investigated and expressed in terms of reduction % of surviving number (CFU) of the tested organisms. More than 98.5% reduction in CFU was observed against the organisms compared to TiO2 -free coated paper.